Tissue Remodeling in Chronic Eosinophilic Esophageal Inflammation: Parallels in Asthma and Therapeutic Perspectives - Nhu, Quan M.; Aceves, Seema S. (Frontiers in Medicine, 2017)
Chronic eosinophilic inflammation is associated with tissue remodeling and fibrosis in a number of chronic T-helper type 2 (Th2)-mediated diseases including eosinophilic esophagitis (EoE) and asthma. Chronic inflammation results in dysregulated tissue healing, leading to fibrosis and end organ dysfunction, manifesting clinically as irreversible airway obstruction in asthma and as esophageal rigidity, strictures, narrowing, dysmotility, dysphagia and food impactions in EoE. Current therapies for EoE and asthma center on reducing inflammation-driven tissue remodeling and fibrosis with corticosteroids, coupled with symptomatic control and allergen avoidance. Additional control of Th2 inflammation can be achieved in select asthma patients with biologic therapies such as anti-IL-5 and -13 antibodies, which have also been trialed in EoE. Recent molecular analysis suggests an emerging role for structural cell dysfunction, either inherited or acquired, in the pathogenesis and progression of EoE and asthma tissue remodeling. In addition, new data suggest that inflammation-independent end organ rigidity can alter structural cell function. Herein, we review emerging data and concepts for the pathogenesis of tissue remodeling and fibrosis primarily in EoE and relevant pathogenetic parallels in asthma, focusing additionally on emerging disease-specific therapies and the ability of these therapies to reduce tissue remodeling in subsets of patients.